Exploring privacy concern and intention in disclosing health information online in Malaysia / Romainor Ismail - Ismail, Romainor (2013)
With rapid development in Information, Communication and Technology (ICT), health industry has become significantly impacted when relevant medical information is stored and retrieved borderlessly. This scenario has triggered many challenges. One of the key challenges is the protection of the medical information which it should be kept private and fully safeguarded. Privacy concerns came from many perspectives such as data violation or invasion via communication tools etc. Therefore, policy has been built in order to improve people trust and reduce privacy concern. Research indicates that privacy concern could impact the decision in disclosing health information online. Therefore, the objective of this study is to investigate the level of privacy concerns and intention in disclosing health information online. The scope of the study focuses on privacy concern and its association with intention to disclose health information online among Malaysian citizen. This research use mixed-method. Quantitative and qualitative approaches were used in the investigation. Sample of 300 respondents have been gathered and 5 personnel were selected for qualitative interviewing. The result shows that different levels of privacy concern exist among Malaysian. In addition, the intention to disclose health information also varies among Malaysian. Future research includes investigating other factors such as culture that may influence the privacy concern among Malaysian.